Empowerment Scale for Pregnant Adolescents: Psychometric Testing on Antenatal Care and Birth Attendant Choices - Fatiah Handayani handayani; Endang Sutisna Sulaeman; Sri Mulyani; Eti Poncorini Pamungkasari (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Inability of pregnant adolescents to make decisions regarding antenatal care and the choice of birth attendants increases the risk of maternal and childbirth complications. This study aimed to develop and validate an empowerment measurement instrument based on the Cattaneo and Chapman framework. A quantitative approach was applied in three community health centers (Puskesmas) in Cimahi City, known for high adolescent pregnancy rates. Data were collected by three community volunteers who distributed questionnaires directly and via Google Forms. Instrument validity was examined through a readability test with 10 adolescents and face validity by four experts. Thirty pregnant adolescents participated. Reliability was tested using Cronbach’s alpha. The empowerment construct produced 40 statements; the Item-Total Correlation test revealed one invalid self-efficacy item, two knowledge items, two skill items, one action item, and three impact items. The overall Cronbach’s alpha was 0.92, with subscales: meaningful goals (0.84), self-efficacy (0.58), knowledge (0.70), skills (0.52), action (0.77), and impact (0.83). This study concludes that the empowerment instrument is valid and reliable, and further research is recommended to revalidate it through content validity and factor analysis with larger samples